2015
DOI: 10.7897/2277-4343.06124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lethal Activity of Psidium Guajava Linn. Extracts on Bacterial Pathogens Causing Diarrheal Infections

Abstract: Treatment of diarrheal infections is often challenged by development of drug resistance among the bacteria. The aim of this study was to investigate the antibacterial property of extracts of guava (Psidium guajava Linn.) leaves against diarrhea causing bacterial pathogens. Four extracts viz., ethanol, methanol, ethyl acetate and hot water extract of guava leaf were assayed for antibacterial activity against three selected bacterial pathogens along with four commercial antibiotics. The methanol extract exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
4
2
Order By: Relevance
“…Moreover, other studies also demonstrated the antimicrobial effect of some bacteria that cause gastrointestinal disorders by different methods [ 34 , 35 ]. In contrast to previous results [ 20 , 31 ], no inhibition of the hydrodistillation and n-hexane extract was found against E. coli Salmonella spp. [ 31 ] ( Table 1 ).…”
Section: Pharmacological Propertiescontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, other studies also demonstrated the antimicrobial effect of some bacteria that cause gastrointestinal disorders by different methods [ 34 , 35 ]. In contrast to previous results [ 20 , 31 ], no inhibition of the hydrodistillation and n-hexane extract was found against E. coli Salmonella spp. [ 31 ] ( Table 1 ).…”
Section: Pharmacological Propertiescontrasting
confidence: 99%
“…In contrast to previous results [ 20 , 31 ], no inhibition of the hydrodistillation and n-hexane extract was found against E. coli Salmonella spp. [ 31 ] ( Table 1 ).…”
Section: Pharmacological Propertiescontrasting
confidence: 99%
See 2 more Smart Citations
“…Chemically it is 5, 7, 3, 4, tetrahydroxy flavonol -3-rhamanoglucoside ( Figure 1) and widely used in medicine for maintenance of capillary integrity. It possesses anti-inflammatory, antihepatotoxic 2 , antiulcer 3 , antiallergic and antiviral actions and some of them provide protection against cardiovascular mortality [4][5][6] . It also has antioxidant activity and reduces low density lipoproteins [LDL] oxidation 7 .…”
Section: Introductionmentioning
confidence: 99%